2023
DOI: 10.2147/jir.s397327
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lncRNA-miRNA-mRNA Expression in the Troxerutin-Mediated Prevention of Radiation-Induced Lung Injury in Mice

Abstract: Background Radiation-induced lung injury (RILI) is a critical factor that leads to pulmonary fibrosis and other diseases. LncRNAs and miRNAs contribute to normal tissue damage caused by ionizing radiation. Troxerutin offers protection against radiation; however, its underlying mechanism remains largely undetermined. Methods We established a model of RILI in mice pretreated with troxerutin. The lung tissue was extracted for RNA sequencing, and an RNA library was construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Various pharmacological treatments have been reported to improve disease status (such as osteosarcoma, radiation‐induced lung injury, and diabetic nephropathy 90 , 91 , 92 ) through miRNA regulation. It was demonstrated that both telmisartan and linagliptin (dipeptidyl peptidase‐4 inhibitor, glucose‐lowering medication) induce restorative effects on anti‐fibrotic miR‐29c expression, 92 attenuating disease progression in diabetic nephropathy.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…Various pharmacological treatments have been reported to improve disease status (such as osteosarcoma, radiation‐induced lung injury, and diabetic nephropathy 90 , 91 , 92 ) through miRNA regulation. It was demonstrated that both telmisartan and linagliptin (dipeptidyl peptidase‐4 inhibitor, glucose‐lowering medication) induce restorative effects on anti‐fibrotic miR‐29c expression, 92 attenuating disease progression in diabetic nephropathy.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%